Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3892/or.2019.7427
|View full text |Cite
|
Sign up to set email alerts
|

BMP9 mediates the anticancer activity of evodiamine through HIF‑1α/p53 in human colon cancer cells

Abstract: Colon cancer is one of the most common malignancies. Although there has been great development in treatment regimens over the last few decades, its prognosis remains poor. There is still a clinical need to find new drugs for colon cancer. Evodiamine (Evo) is a quinolone alkaloid extracted from the traditional herbal medicine plant Evodia rutaecarpa. In the present study, CCK-8, flow cytometry, reverse transcription quantitative polymerase chain reaction, western blot analysis and a xenograft tumor model were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…This is in line with the aggressive course of disease of P090, as well as published results from a different cohort 23 . Interestingly, a correlation between BMP‐9 and p53 has been described earlier by Li et al 43 : in a human CRC cell line (HCT116), BMP‐9 promotes p53 activity and thereby reduces tumour growth in a xenotransplantation mouse model.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with the aggressive course of disease of P090, as well as published results from a different cohort 23 . Interestingly, a correlation between BMP‐9 and p53 has been described earlier by Li et al 43 : in a human CRC cell line (HCT116), BMP‐9 promotes p53 activity and thereby reduces tumour growth in a xenotransplantation mouse model.…”
Section: Discussionsupporting
confidence: 87%
“…By treating HCT116 cells with Evo and using these cells to induce cancer in a mouse model following injection into the hip, the mechanism of the anticancer effect in CRC of Evo and BMP9 was investigated. In those experiments where BMP9 was overexpressed or silenced in HCT116, the antitumor action of Evo, its upregulation of HIF-α and its activation of the oncosuppressor p53 increased with BMP9 and was decreased by silencing BMP9 [52].…”
Section: Bmp9mentioning
confidence: 98%
“…The involvement of BMP9 in colonic tumorigenesis has also been highlighted by an interesting and recent study on the potential beneficial anti-neoplastic effects of a natural component against CRC [52]. This study demonstrated that evodiamine (Evo), a quinolone alkaloid extracted from traditional herbal medicine Evodia rutaecarpa, had an antitumor activity, and the authors tried to elucidate its molecular mechanisms.…”
Section: Bmp9mentioning
confidence: 98%
“…In line with this, the 4-(2-phenylpyridin-4-yl)pyrazoles exerted antiproliferation and apoptosis-inducing effect by inhibiting the activation of HIF-1 α in HCT116 cells [ 43 ]. However, the evodiamine treatment suppressed proliferation and induced apoptosis by upregulating bone morphogenetic protein 9 (BMP9), which could activate p53 via the upregulation of the HIF-1 α in HCT116 cells [ 44 ].…”
Section: The Role Of Hifs In the Gtmentioning
confidence: 99%